Exploring a sensitive issue: menopause experience among urban Malay women in Malaysia - Mohamad Diah, Nurazzura (2007)
This paper aims to explore the practicalities of using qualitative methodology, specifically in-depth interviews and participant observation, in researching a sensitive issue. This method was chosen in order to gain an understanding of menopausal experiences among urban Malay women. Generally, menopause is not discussed openly in the Malay society. However, other areas of reproductive health like fertility, childbirth and post-partum experience are spoken about publicly, making menopause an area of relatively marginal concern in regards to women’s health. Researching a sensitive issue like menopause is therefore taxing and at times overwhelming. Reluctance to discuss the issue is the first of a number of challenges faced in researching the topic. This paper examines these challenges which include recruiting participants into the study, building trust and rapport, and communicating effectively with participants throughout the fieldwork. Some strategies used to overcome the challenges are included in the paper. The most important of these is the justification of the research topic. Menopause can be of concern to many women. Given the changing demographics of the ageing society and women continued and important place in the workforce, the health of menopausal women should be taken seriously and open discussion will help to improve this situation. The paper concludes that qualitative methodology enables us to gain new information not accessible through other methods of data collection, especially for topics that are of a sensitive nature like menopause.